(3ZjK GdCOH GdPj CfSLe aj TQM dGejI GdYLes - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s; (3GdWZQGFj , GdMSjf Hf Ydj Hf eMeO Hf YHO GdUeO GdCUHgGfj GdWZQGfj, eDjO GdOjf CHh ESeGYjd,J (B513 (3g` s
(3ChdgG (B:s
(3SCHcjc ef hbJ GdUHhM hEffj SCcKQ ef hbJ GdZHhb dc GdfOHG s
(3BNQgG (B:s
(3hda aj GdHQOI CYWGag MJi jWjH GdfTQ ef dag ced ZjK GdCOH GdPj CfSLe aj TQM dGejI GdYLe s
(3HBNQgG bUjOI GdWZQGFj GdeTQhMIs
(3fSNI KGdKIs
(3JJab aj BNQgG eY GdfSNI GdChdi HGNJdGa aj HYV GdCdaGXs
(3hHgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GdCOHs